2021
DOI: 10.1371/journal.pone.0255170
|View full text |Cite
|
Sign up to set email alerts
|

Update: Gender differences in CABG outcomes—Have we bridged the gap?

Abstract: Background Appreciation of unique presentation, patterns and underlying pathophysiology of coronary artery disease in women has driven gender based risk stratification and risk reduction efforts over the last decade. Data regarding whether these advances have resulted in unequivocal improvements in outcomes of CABG in women is conflicting. The objective of our study was to assess gender differences in post-operative outcomes following CABG. Methods Retrospective analyses of institutional data housed in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
(42 reference statements)
2
14
2
Order By: Relevance
“…Several observational studies reported higher 30-day mortality rates in women [26][27][28][29][30]. We could not confirm this result based on our data in line with other studies [2,[31][32][33]. The unadjusted and the overlap weighted cohorts presented similar in-hospital mortality rates.…”
Section: Plos Onecontrasting
confidence: 91%
See 1 more Smart Citation
“…Several observational studies reported higher 30-day mortality rates in women [26][27][28][29][30]. We could not confirm this result based on our data in line with other studies [2,[31][32][33]. The unadjusted and the overlap weighted cohorts presented similar in-hospital mortality rates.…”
Section: Plos Onecontrasting
confidence: 91%
“…As documented in other series, women represented about 25% of patients undergoing CABG from 2000 to 2015 [25,33]. Whether this might represent a referral bias is not supported by our data.…”
Section: Plos Onecontrasting
confidence: 39%
“…Female sex has previously been associated with increased cardiovascular mortality and morbidity after CABG (4,5,23).…”
Section: Discussionmentioning
confidence: 97%
“…Outcomes of coronary heart disease (CHD) and coronary artery bypass crafting (CABG) have constantly improved over the past decades ( 1 3 ). However, women’s prognosis after coronary events and revascularizations, including CABG, still remain markedly impaired compared to that of men ( 4 , 5 ). The mechanisms explaining this observed sex difference are undoubtedly multifactorial and partially related to older age at the time of surgery and greater comorbidity ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation